Over-Expression of a Wheat Late Maturity Alpha-Amylase Type 1 Impact on Starch Properties During Grain Development and Germination - Zhang, Qin; Pritchard, Jenifer; Mieog, Jos; Byrne, Keren; Colgrave, Michelle L.; Wang, Ji-Rui; Ral, Jean-Philippe F. (Frontiers in Plant Science, 2022)
The hydrolysis of starch is a complex process requiring synergistic action of multiple hydrolytic enzymes including α-amylases. Wheat over-expression of TaAmy1 driven by seed specific promoter resulted in a 20- to 230-fold of total α-amylase activity in mature grains. Ectopic expression of TaAmy1 showed a significant elevated α-amylase activity in stem and leaf without consequences on transitory starch. In mature grain, overexpressed TaAMY1 was located mainly in the endosperm with high expression of TaAmy1 from early developing grains having effect on starch granules from 18 DPA and on soluble sugar accumulation from 30 DPA. While accumulation of TaAMY1 led to a high degree of damaged starch in grains, the dramatic alterations of starch visco-properties caused by the elevated levels of α-amylase occurred essentially during processing thus suggesting a very small impact of related starch damage on grain properties. Abnormal accumulation of soluble sugar (α-gluco-oligosaccharide and sucrose) by TaAMY1 over-expression reduced the grain dormancy and enhanced abscisic acid (ABA) resistance. Germination study in presence of alpha-amylase inhibitor suggested a very limited role of TaAMY1 in the early germination process and starch conversion into soluble sugars.